153k views
5 votes
Use the function to find f(-2)

Use the function to find f(-2)-example-1
User Paradoxis
by
6.8k points

2 Answers

2 votes

Answer:


(1)/(9)

Explanation:

  1. Substitute the -2 into the equation.
    f(-2)=3^(-2)
  2. Begin to simplify the exponent.
    x^(-y)=(1)/(x^y), so you get
    f(-2)=(1)/(3^2)
  3. Finish simplifying the exponent. 3 times 3 is 9.
    f(-2)=(1)/(9)
User Richard Askew
by
7.1k points
5 votes

Answer:

f(-2) = 1/9

Explanation:

Plug in -2 to x in the equation:

f(x) = 3^x

f(-2) = 3^(-2)

Solve. Note that if there is a negative in the power, you must flip the "fraction" and set it over 1. The answer itself does not become negative:

f(-2) = 1/(3^2)

f(-2) = 1/(9)

f(-2) = 1/9 is your answer.

~

User Josh Part
by
6.4k points